HDTV - ready for the long drive?. - Wolfe, A.
HDTV seems poised at last to penetrate the US mass market. Its advent has been predicted so many times in the past, often with breathless enthusiasm, that any claims made for it now are bound to meet with healthy skepticism. It has so far failed to meet every milestone set for its introduction, and the 2006 deadline for a complete switchover to HDTV threatens to be no exception. However, a large number of basic factors would seem to be combining to give HDTV the critical mass for liftoff: more programs, readiness of cable and satellite services to provide distribution, cheaper receivers, consumer-friendly regulation, and the imminent arrival of the first DVD recorders capable of handling HDTV.
Keywords: DVD recorders; HDTV distribution; HDTV receivers; US mass market; Cable services; Consumer-friendly regulation; Satellite services